Pendampingan Pembuatan Produk Bosara Bersama Ibu Pkk Di Desa Barambang - Alda Lestari; Srianti Permata; Jumardi (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
One activity that is very well developed is the Bosara Business which is a craft business that has been developed since the past until now. At first, bossara crafts were only made of palm leaves, but over time, bosara crafts were finally made of iron frames which were then given cloth as edges and flowers and decorated with lace as edges and flowers and rings as handles which were attached using wax glue. The fabrics used are of various types, such as boarding cloth, organza cloth and lace cloth. The purpose of holding bosara-making mentoring activities is to empower target audiences to have knowledge about the importance of taking advantage of free time, making use of leftovers, with possessive activities that can bring in profits or additional income, by making handicrafts, namely bosara especially for mothers. PKK mother. PKK mother. The method used in community service is divided into three stages: the first stage is observation of PKK mothers, the second stage is the preparatory stage where community service participants prepare the materials needed during assistance, then the third stage is the implementation stage of making bosara, which was carried out in one of the mosques in Barambang Village together with PKK members. The number of PKK women who attended was 10 people at the assistance site in Barambang Village, Sinjai Borong sub-district, and the number of bosara that was successfully made was 3 bosara